Novel population of small tumour-initiating stem cells in the ovaries of women with borderline ovarian cancer - Virant-Klun, Irma (Sci Rep, 2016)
Small stem cells with diameters of up to 5 μm previously isolated from adult human ovaries indicated pluripotency and germinal lineage, especially primordial germ cells, and developed into primitive oocyte-like cells in vitro. Here, we show that a comparable population of small stem cells can be found in the ovarian tissue of women with borderline ovarian cancer, which, in contrast to small stem cells in “healthy” ovaries, formed spontaneous tumour-like structures and expressed some markers related to pluripotency and germinal lineage. The gene expression profile of these small putative cancer stem cells differed from similar cells sorted from “healthy” ovaries by 132 upregulated and 97 downregulated genes, including some important forkhead box and homeobox genes related to transcription regulation, developmental processes, embryogenesis, and ovarian cancer. These putative cancer stem cells are suggested to be a novel population of ovarian tumour-initiating cells in humans.